Sistema de gestión académica para la enseñanza secundaria básica de la provincia de Granma - Uribe Robayo, Patricia Jeaneth (2013)
In actuality don´t exist software who manages the docent secretary business for Education Ministry, who manage the information about secretary docent in the junior school. The information volume managed for this department is enormous in student number correlation. The problem situation defines the general objective of this investigation who: Developer one Manage Academic System for make easy the work developed in docent secretary in the Senior School in the province of Granma. This application was developed using free technology, using Java who programing language, PostgreSQL who database and Apache Tomcat who application server. The most important contribution for this investigation was gift to the Secondary School one tool for the information manages about the learned-teaching process make easy the work to the docent secretary and gives information to the student life cycle.